Search for Universal Extra Dimensions in p(p)over-bar Collisions - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Watts, G.; et al. (Amer Physical Soc, 2012)
We present a search for Kaluza-Klein (KK) particles predicted by models with universal extra dimensions (UED) using a data set corresponding to an integrated luminosity of 7.3 fb(-1), collected by the D0 detector at a p (p) over bar center-of-mass energy of 1.96 TeV. The decay chain of KK particles can lead to a final state with two muons of the same charge. This signature is used to set a lower limit on the compactification scale of R-1 > 260 GeV in a minimal UED model.